2018
DOI: 10.1186/s12936-018-2361-y
|View full text |Cite
|
Sign up to set email alerts
|

Costs and cost-effectiveness of malaria reactive case detection using loop-mediated isothermal amplification compared to microscopy in the low transmission setting of Aceh Province, Indonesia

Abstract: BackgroundReactive case detection (RACD) is an active case finding strategy where households and neighbours of a passively identified case (index case) are screened to identify and treat additional malaria infections with the goal of gathering surveillance information and potentially reducing further transmission. Although it is widely considered a key strategy in low burden settings, little is known about the costs and the cost-effectiveness of different diagnostic methods used for RACD. The aims of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
0
33
1
Order By: Relevance
“…However, due the low prevalence of infection in this region of Colombia, there is also a need to evaluate the costs per assay comparing to conventional test, including equipment, reagents, staff, training, and maintenance in order to evaluate the cost-effectiveness of molecular test for their potential integration into surveillance strategies and explore alternatives as serological surveillance. A previous study in a low transmission setting in Indonesia, suggested that reactive-active detection of cases in the community using molecular test had high costs per individual screened, however, compared to microscopy, molecular test was most cost-effective for the detection of infections [43]. Also, another study in a low transmission setting in Africa concludes that standards test, such as rapid diagnosis test (RDTs), are not useful to detect infections in the community and suggest that the achievement of malaria elimination may require active case detection using more sensitive pointof-care diagnostics, especially in high-risk groups [44], that in our cases are the indigenous communities among others.…”
Section: Discussionmentioning
confidence: 99%
“…However, due the low prevalence of infection in this region of Colombia, there is also a need to evaluate the costs per assay comparing to conventional test, including equipment, reagents, staff, training, and maintenance in order to evaluate the cost-effectiveness of molecular test for their potential integration into surveillance strategies and explore alternatives as serological surveillance. A previous study in a low transmission setting in Indonesia, suggested that reactive-active detection of cases in the community using molecular test had high costs per individual screened, however, compared to microscopy, molecular test was most cost-effective for the detection of infections [43]. Also, another study in a low transmission setting in Africa concludes that standards test, such as rapid diagnosis test (RDTs), are not useful to detect infections in the community and suggest that the achievement of malaria elimination may require active case detection using more sensitive pointof-care diagnostics, especially in high-risk groups [44], that in our cases are the indigenous communities among others.…”
Section: Discussionmentioning
confidence: 99%
“…This focus on infectious sources is quite different from that in parts of Africa that are still in the epidemic stage. Malaria-endemic areas in Africa mainly concentrate on epidemic surveillance, which emphasizes blocking infectious sources, controlling transmission routes, and protecting susceptible populations (19,22,23). In the malaria elimination phase, on the other hand, staff should adopt more targeted surveillance measures, focusing on the screening and detection of imported infectious sources.…”
Section: Discussionmentioning
confidence: 99%
“…The application of RCD in many of these settings differs in important features, such as the optimal screening radius and the number of households investigated [10]. In each instance, however, RCD is labour and time-intensive, requiring significant human resources, many rapid diagnostic tests (RDTs), and often long travel times between households [10,11]. The utility of RCD in low transmission settings has been debated in part due to operational challenges during implementation and the use of less sensitive diagnostic tools such as RDTs and microscopy, which miss low density infections [1,2,10,12].…”
Section: Introductionmentioning
confidence: 99%